(untitled) (Tarbiyah Suska Conference Series, 2023)
The research in this paper discusses the vision of the National Education System in Islamic Education after the birth of the SISDIKNAS Law No. 20 of 2003 using the literature review method. As for the research results, the delivery of the National Education System Law No. 20 of 2003 replaced Law no. 2 of 1989, which has confirmed the existence of Islamic Education in Indonesia. This can be seen in three things. First, Law no. 20 of 2003 explicitly mentions several Islamic educational institutions, including Madrasahs, Raudatul Atfal, Taklim Council and Islamic Boarding Schools. Second, Law no. 20 of 2003 also clearly states that Islamic religious education material must be taught to all types and levels of education. Third, in Law no. 20 of 2003 contains many values that align with Islamic values.